Role of film thickness on the structural and optical properties of GaN on Si (100) grown by hollow-cathode plasma-assisted atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2018)
In this study, the authors report on the evolution of crystallinity, chemical composition, surface morphology, and optical properties of highly oriented (002) GaN films as a function of film thickness, ranging from 5.37 to 81.40 nm deposited on Si substrates via low-temperature hollow-cathode plasma-assisted atomic layer deposition (HCPA-ALD). GaN thin films were prepared using a sequential injection of triethyl gallium and N-2/H-2 plasma within the self-limited growth regime, i.e., ALD window at 200 degrees C. The grazing-incidence x-ray diffraction (GIXRD) analysis reveals that GaN films have a (002) preferential growth direction and the crystalline quality of GaN films was improved with the increase in thickness. GIXRD and atomic force microscopy confirmed the presence of GaN grains, and the grain size increases when the thickness of the GaN layer increases from 5.37 to 48.65 nm. From the x-ray photoelectron spectra, it was shown that the amount of oxygen incorporated in the GaN film decreases as the thickness increases. The spectroscopic ellipsometry analysis reveals that the optical film density and local crystallinity was improved with increasing film thickness to 48.65 nm, but further increase in the film thickness does not seem to improve these features. The optical band edge results suggested that bandgap widening is valid for all HCPA-ALD grown GaN samples. The overall results suggested that GaN films with thicknesses above 48.65 nm have different behavior compared to the thinner GaN films. Published by the AVS.
Keywords: LOW-TEMPERATURE GROWTH; HEXAGONAL GAN; DIELECTRIC FUNCTION; VAPOR-DEPOSITION; CRYSTALLINE ALN; THIN-FILMS; CONSTANTS; HETEROSTRUCTURE; SAPPHIRE